7 Themes of Depression Female Students Residing in A Dormitory: A Qualitative Iterpretative Phenomenological Analysis - Walukouw, Yane Restuwaty (Peneliti.net, 2024)
Depression is a debilitating and distressing illness that profoundly impacts the abilities and academic pursuits of adolescents. Manifesting in various aspects, such as physical, emotional, cognitive, behavioral, and social domains, depression disrupts academic functioning and impedes learning. This research employs a phenomenology qualitative approach with semi-structured interviews to gather data. The study involves six female adolescents, aged 18 to 20, who are experiencing depression, based on diagnosed by the doctor and who are enrolled as students in an Adventist University in Indonesia during 2022-2023 academic year. The primary objective of this study is to gain a qualitative understanding of depression in female adolescents. By doing so, faculty members can develop a deeper comprehension of how to effectively support and assist students dealing with depression. The following 6 themes such as ”Family Condition”, “Dormitory Condition”. “Feeling hopeless and helpless”, “An experience of loneliness and isolation”, “Feeling unworthy”, and “Therapy as a last resort.” The feeling that they have to deal with it by themselves, and/or the lack of caring who support the students in getting help. The finding suggested the ongoing importance of reducing stigma and promoting mental health education for the students as well as their parents, deans of dormitory, school staff, and dormitorian. It seems that the present research implicity opens away to explore and to understand the inter subjectivity of students as an important part of dormitory society.